Agronomic Performance of Corn Population Selected for Nutrient Efficiency in Marginal Land - Renih Hayati; , Munandar; Fitria K. S. Lestari (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2009)
Low soil fertility is the most important factor constraining corn (Zea mays L.) yield in marginal land due to soil acidity. Corn cultivars with high nutrient efficiency and tolerance to soil acidity offer an alternative to solve the problem. A Complex population had been formed by natural crossing among six cultivars/line expected to carry the nutrient efficiency character; Sukmaraga, Lamuru, Srikandi Kuning, Bisma, Bayu, and Toray and used as a genetic material in this study. The objectives were (i) to evaluate the agronomic performance of complex population in marginal land under limited nutrient supply, (ii) to select the superior entries in each population for nutrient efficiency, and (iii) to identify the characters relate to yield (nutrient efficiency). The selection of nutrient efficiency was based on the ear dry weight produced per plant (yield). The experiment was conducted in marginal land at Agro Techno Park, Indralaya, South Sumatra in January to April 2008. Randomized Complete Block Design with four replications was used. The treatment was number of entries that grouped into six populations based on a female parent. Plants were fertilized with Urea, SP-36, and KCl at 30% of standard rate. Sukmaraga population had the best agronomic performance among six populations evaluated. The superior entries selected were top 10% of the total entries in each population with ear weight more than 150 g. All the characters (ear length and diameter, plant height, leaf chlorophyll, leaf numbers above the ear, and ear leaf area) related to yield (nutrient efficiency) but plant height is the only character measured before anthesis. The results suggest that Sukmaraga population had use nutrient more efficiently than the other populations and plant height may be used as selection criterion in early screening large numbers of corn entries or lines for nutrient efficiency. Key words: Agronomic characters, corn, marginal land, nutrient efficiency